ANALYSIS OF MANGROVE DAMAGE AND DIVERSITY IN THE MANGROVE FOREST AREA OF TANJUNG SOLOK VILLAGE, KUALA JAMBI SUB-DISTRICT - Rahayu Sindy; Mahya Ihsan; Madyawati Latief (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Mangrove forests are tropical coastal vegetation communities consisting of several species that are able to grow and develop in muddy tidal areas. Coastal areas have a variety of community activities in utilizing coastal natural resources in the economic sector. Social condition factors and lack of understanding of the functions and benefits of mangroves also affect the damage to mangrove ecosystems. This directly causes ecological impacts that threaten the sustainability of mangrove forests. The purpose of this study was to analyze the damage and diversity of mangroves in the mangrove ecosystem area of Tanjung Solok Village. This research method uses indepth interview techniques, and observation in the field with data collection including documentation and sample identification. The results showed that the damage to mangrove ecosystems in Tanjung Solok Village, Kuala Jambi District was categorized as low or damaged, because the results obtained tree density <1000 trees/ha. This is caused by activity factors and lack of knowledge of the surrounding community. As well as the level of diversity (H') obtained in Tanjung Solok Village, Kuala Jambi District, obtained a value of 2.033. This shows that the level of diversity of mangrove vegetation in Tanjung Solok Village, Kuala Jambi Subdistrict is in the medium category. Keyword: Mangrove diversity, coastal ecosystems, mangrove malfunction